ANALISIS TINGKAT KEMAMPUAN SHOOTING ATLET PETANQUE - Lina Ulpiana; Andi Gilang Permadi; Muhammad Asy’ari (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Shooting is the most important part of the petanque game if in one team the shooting ability of the athlete is weak, then the team will have difficulty attacking the opponent's ball, therefore high concentration is needed in petanque sports, especially when shooting. Based on the formulation of the problem, how is the shooting ability level of the MBC East Lombok Petanque athlete in 2021, this study aims to determine the level of shooting ability of the MBC East Lombok Petanque athlete in 2021. The research design measures the shooting ability of the MBC Petanque athlete by conducting a series of tests that the researcher has determined. The research method uses descriptive quantitative research, the population of the MBC club and uses purposive sampling using 8 samples that act as shooters, with data collection techniques using observation, action methods and documentation. The instrument used is a shooting game test (Souef, 2015:85). The data obtained for each test item is raw data then converted into a t-score value and interpreted by categorizing the data. Based on the results of the study, it can be concluded that the level of shooting ability of the MBC Lombok Timur Petanque athletes in 2021. The basic shooting technique ability on the average level of shooting ability of the MBC Lombok Timur Petanque athletes in 2021 is 16.50. The percentage of petanque game shooting abilities in MBC Lombok Timur petanque athletes are: 5 athletes (50.0%) in good category, 2 athletes (30.0%) in moderate category, and 1 athlete (20.0%) with less category. So it can be concluded that the level of shooting ability of MBC East Lombok Petanque athletes in 2021 is in the good category.